IMPLEMENTASI WEB SERVICE PADA SISTEM INFORMASI AKADEMIK UNIVERSITAS STIKUBANK (UNISBANK) SEMARANG (Information Technology and Telematics, 2015)
Abstract : Service information about academic is a very important service to the academic activities at the Stikubank University (UNISBANK) Semarang. With this service can find out information on the progress of students study. However, the data can only be accessed by one application. Web service is used as a facility provided by a system to provide services (in the form of information) to other systems, so that other systems can interact with the system through the services provided by the system that provides the web service. In this research system is designed using the system architecture, data flow diagrams, and flowcharts. The results of the system design is a web service application that processes the data from the of academic information system Stikubank University (UNISBANK) Semarang with the end result is a json file that can be used by other applications. Keyword : web service, json